Gratitude across the life span: Age differences and links to subjective well-being. Issue 3 (4th May 2019) - Chopik, William J.; Newton, Nicky J.; Ryan, Lindsay H.; Kashdan, Todd B.; Jarden, Aaron J.
Abstract: Gratitude has been described as an adaptive evolutionary mechanism that is relevant to healthy psychological and interpersonal outcomes. Questions remain as to whether the presence and benefits of gratitude are consistent from young adulthood to old age; prior research has yielded mixed evidence. We examined the magnitude and direction of age differences in gratitude in three samples (combined N  = 31, 206). We also examined whether gratitude was associated with greater/lesser well-being at different periods in the life course. We found that the experience of gratitude was greatest in older adults and least in middle aged and younger adults. Further, we found that the associations between gratitude and subjective well-being remained relatively constant across the lifespan. Findings are discussed from a developmental perspective.